Dynamics of Initial Swimming Readiness of Junior School Children in the School Sports Club - Shkrebtiy, Yuriy; Korolchuk, Bohdan; Nosova, Nataliia; Huzak, Oleksandra; Lazakovych, Yuliia; Rodionenko, Mykhaylo; Plyeshakova, Olena (Physical Education Theory and Methodology, 2023)
The purpose of the study was to estimate the effect of swimming lessons in a school sports club on the initial swimming fitness of primary school-aged children. Materials and methods. The study participants were 73 primary school-aged children (‘Sportrend’ school sports swimming club). The study used theoretical analysis of scientific and methodological literature, the system of control exercises by O. Obrazhei revised taking into account the contingent of the research to assess the swimming fitness of primary school students under the conditions of a school sports club, and methods of mathematical statistics. Results. We propose a methodology for assessing the swimming readiness of younger schoolchildren under the conditions of a school sports club. The growth rate of such indicators as reaction to the unsupported position in the water and underwater breath-holding turned out to be lower compared to other indicators. At the same time, the rates of face submersion in the water and squatting in the water increased. The increase in initial swimming skills in children was 49.3% at the control stage compared to the baseline, and the average growth rate was 22.2%. In the assessment of children’s initial skills at the end of the training compared to the beginning, the maximum average rate of increase was recorded for the ability to push off and slide (30.1%), the ability to perform a star float (27.4%), and squatting in the water (26.4%), thus swimming lessons have a positive effect on the initial swimming readiness of junior school students. Conclusions. Statistically significant (p<0.05) improvement of primary school students’ results on control exercises at all stages of diagnostics of their initial swimming skills formation confirms the positive effect of swimming lessons in a school sports club.